Risk of Bleeding Associated With Ibrutinib in Patients With B-Cell Malignancies: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Jinjin; Zhao, Ailin; Zhou, Hui; Zhu, Jinbing; Niu, Ting (Frontiers in Pharmacology, 2020)
Background: Ibrutinib is an oral covalent Bruton tyrosine kinase (BTK)inhibitor that has been approved for chronic lymphocytic leukemia/small lymphocytic leukemia (CLL/SLL) and some other B-cell malignancies. Some studies have found an increased risk of bleeding with ibrutinib. However, some literatures found no significant differences in the risk of major bleeding in patients treated with ibrutinib compared with other regimens. So, we performed a systematic review and meta-analysis of randomized controlled trials (RCTs)to estimate the risk of bleeding associated with ibrutinib in patients with B-cell malignancies. Methods: A systematic search of PUBMED, EMBASE, Central Register of Controlled Trials (CENTRAL) and ClinicalTrials.gov was performed through February 2020, to identify randomized controlled trials comparing ibrutinib with other agents or placebo in B-cell malignancies. The RevMan software (version 5.3) was used to carry out this analysis and the analyzed data were represented by risk ratios (RR)and 95% confidence intervals (CI). Results: There were 11 eligible RCTs(4288 patients),all studies reported major bleeding, and 7 studies reported overall bleeding(any grade bleeding).Ibrutinib was associated with a significantly increased risk of bleeding(overall bleeding and major bleeding)in patients with B-cell malignancies[RR=2.56,95%CI 1.68-3.90,P＜0.0001;and RR=2.08,95%CI 1.36-3.16,P=0.0006,respectively].The bleeding(overall bleeding and major bleeding) risk in patients with chronic lymphocytic leukemia was more obvious[RR=3.08,95%CI 2.07-4.58,P＜0.00001;and RR=2.46,95% CI 1.37-4.41,P=0.003,respectively].The risk of bleeding were no statistically significant difference between subgroups based on dose and treatment setting. Conclusions: ibrutinib was associated with a significantly higher risk of bleeding (both overall bleeding and major bleeding) in patients with B-cell malignancies, especially in chronic lymphocytic leukemia.